Generalized discrete equivalent model for PV system with various types of faults and PV penetration levels - Fu Shen; Zhiwen Yang; Shiwei Li; Guangbing Yang (Frontiers in Energy Research, 2023)
As the rapid and continually proliferation of photovoltaic (PV) systems are connected to the power system, the load structure are changeable to lack an accurate dynamic discrete equivalent model to describe its characteristics of power grid. In this study, the generalized discrete-time equivalent model (GDEM) of PV system using a fourth-order dynamic equivalent model for representing the physical characteristics of PV power stations are proposed in power system dynamic studies. The paper then investigates the inherent relations among GDEM parameters in the discrete-time models of PV system to facilitate the GDEM parameters estimation in PV system. Finally, the least square method (LSM) was to identify the GDEM of PV system parameters, and various types of ground faults and PV penetration rate levels is adopted to verify the dynamic characteristics of the proposed GDEM of PV system in power system simulations.